2019
DOI: 10.3174/ajnr.a6153
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Percentage Signal Recovery and Baseline Signal in DSC-MRI Optimized for Relative CBV Measurement for Differentiating Glioblastoma, Lymphoma, Metastasis, and Meningioma

Abstract: BACKGROUND AND PURPOSE: The percentage signal recovery in non-leakage-corrected (no preload, high flip angle, intermediate TE) DSC-MR imaging is known to differ significantly for glioblastoma, metastasis, and primary CNS lymphoma. Because the percentage signal recovery is influenced by preload and pulse sequence parameters, we investigated whether the percentage signal recovery can still differentiate these common contrast-enhancing neoplasms using a DSC-MR imaging protocol designed for relative CBV accuracy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 34 publications
6
42
0
Order By: Relevance
“…The vast majority of these articles investigated the usefulness of so-called advanced MRI methodologies in differentiating low-grade from high-grade gliomas or glioblastomas from brain metastases or meningiomas [ 34 , 35 , 36 ]. Several articles focused on differentiation between GBMs, metastases, and PCNSL [ 37 , 38 , 39 , 40 , 41 , 42 ] and achieved in part excellent diagnostic parameters for this purpose with an area under the receiver operating curve (AUC) of up to 0.98, sensitivity of 100%, specificity of 93%, and accuracy of 95% [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of these articles investigated the usefulness of so-called advanced MRI methodologies in differentiating low-grade from high-grade gliomas or glioblastomas from brain metastases or meningiomas [ 34 , 35 , 36 ]. Several articles focused on differentiation between GBMs, metastases, and PCNSL [ 37 , 38 , 39 , 40 , 41 , 42 ] and achieved in part excellent diagnostic parameters for this purpose with an area under the receiver operating curve (AUC) of up to 0.98, sensitivity of 100%, specificity of 93%, and accuracy of 95% [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 -20 Some authors recently reported an additional parameter directly extracted from TICs termed "peak height," which has shown promising results. 12,15 However, the lack of technique standardization, which causes variability in the identification of the best discriminating parameter and its relevant thresholds between different studies, as well as the lack of a user-friendly way to depict the results, impedes the widespread clinical application of these perfusion parameters. 16,[22][23][24] We obtained satisfactory accuracy values in the comparisons between PCNSL and glioblastoma, anaplastic astrocytoma, metastasis, and meningioma in the test subset.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, parameters derived from DSC-PWI have shown promising results in the diagnosis of brain tumors, and especially PCNSL. [12][13][14][15][16][17][18][19][20] DSC-PWI generates time-intensity curves (TICs) from dynamic monitoring of T2* signal intensity changes during contrast administration. Specific well-known parameters such as relative cerebral blood volume (rCBV) and percentage of signal recovery (PSR) are extracted from these TICs.…”
mentioning
confidence: 99%
“…Therefore, the key to making a distinction between these two tumors appears to lie in detecting the differences within the peritumoral area. 7,9 In recent years, researchers have suggested innovative ways for differentiating between brain tumors using advanced MRI modalities such as diffusion tensor imaging (DTI), [10][11][12] diffusion weighted imaging (DWI), 4,6 perfusion weighted imaging (PWI), [13][14][15][16] magnetic resonance spectroscopy, 17 or a combination of these methods. [18][19][20][21][22][23] Use of these methods, by evaluating tissue microstructure and tumor dynamics, can provide a more accurate evaluation of brain tumors.…”
Section: Introductionmentioning
confidence: 99%